2021
DOI: 10.3389/fimmu.2021.609421
|View full text |Cite
|
Sign up to set email alerts
|

The BCMA-Targeted Fourth-Generation CAR-T Cells Secreting IL-7 and CCL19 for Therapy of Refractory/Recurrent Multiple Myeloma

Abstract: Chimeric antigen receptor (CAR) technology has revolutionized cancer treatment, particularly in malignant hematological tumors. Currently, the BCMA-targeted second-generation CAR-T cells have showed impressive efficacy in the treatment of refractory/relapsed multiple myeloma (R/R MM), but up to 50% relapse remains to be addressed urgently. Here we constructed the BCMA-targeted fourth-generation CAR-T cells expressing IL-7 and CCL19 (i.e., BCMA-7 × 19 CAR-T cells), and demonstrated that BCMA-7 × 19 CAR-T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 58 publications
(62 reference statements)
0
37
0
Order By: Relevance
“…Daun et al. have shown that administration of fourth-generation CAR-T cells expressing IL-7 and CCL19 can remarkably increase the migration and cytotoxicity of CAR-T cells against multiple myeloma and substantially reduce urine protein-light levels in affected patients ( 54 ). Mei et al.…”
Section: Discussionmentioning
confidence: 99%
“…Daun et al. have shown that administration of fourth-generation CAR-T cells expressing IL-7 and CCL19 can remarkably increase the migration and cytotoxicity of CAR-T cells against multiple myeloma and substantially reduce urine protein-light levels in affected patients ( 54 ). Mei et al.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 shows that the cytokine profile of R-MΦs differs from that of GM-MΦs by the secretion of higher levels of chemokines, such as CCL20, CCL19, IL-6, and IL-27. The crucial role played by CCL19 in the immune response is illustrated by its ability with IL-7 to promote tumor infiltration by T cells and dendritic cells and to improve the therapeutic effect of CAR-T cells against solid tumors [ 81 ] or multiple myeloma [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was no clinically significant toxicity. It is worth noticing that this CAR-T cell therapy was associated with a high proportion of stem cell memory (TSCM) among produced CAR-T cells, possibly due to IL-7 production ( 69 ). Indeed, several clinical studies have shown that the modifications to induce differentiation toward a TCM/TSCM profile improve CAR-T cell responses in subjects ( 70 72 ).…”
Section: Challenges and Engineering Strategies To Overcome Car-t Cell...mentioning
confidence: 99%